A mouth sweeter than salt : an African memoir - Falola, Toyin (Book collections on Project MUSE., 2004)
"Toyin Falola has given us what is truly rare in modern African writing: a seriously funny, racy, irreverent package of memories, and full of the most wonderful pieces of poetry and ordinary information. It is a matter of some interest, that the only other volume A Mouth Sweeter Than Salt reminds one of is Ake, by Wole Soyinka. What is it about these Yorubas?"--Ama Ata Aidoo "A splendid coming-of-age story so full of vivid color and emotion, the words seem to dance off the page. But this is not only Falola's memoir; it is an account of a new nation coming into being and the tensions and negotiations that invariably occur between city and country, tradition and modernity, men and women, rich and poor. A truly beautiful book."--Robin D.G. Kelley "More than a personal memoir, this book is a rich minihistory of contemporary Nigeria recorded in delicious detail by a perceptive eyewitness who grew up at the crossroads of many cultures."--Bernth Lindfors "The reader is irresistibly drawn into Falola's world. The prose is lucid. There is humor. This work is sweet. Period."--Ngugi wa Thiongo'o A Mouth Sweeter Than Salt gathers the stories and reflections of the early years of Toyin Falola, the grand historian of Africa and one of the greatest sons of Ibadan, the notable Yoruba city-state in Nigeria. Redefining the autobiographical genre altogether, Falola miraculously weaves together personal, historical, and communal stories, along with political and cultural developments in the period immediately preceding and following Nigeria's independence, to give us a unique and enduring picture of the Yoruba in the mid-twentieth century. This is truly a literary memoir, told in language rich with proverbs, poetry, song, and humor. Falola's memoir is far more than the story of one man's childhood experiences; rather, he presents us with the riches of an entire culture and community-its history, traditions, pleasures, mysteries, household arrangements, forms of power, struggles, and transformations